Association between female urinary urgency and aponeurotic ptosis: Results from a community‐based cross‐sectional study in Japan. Issue 6 (26th June 2021) - Ozaki, Yusuke; Okamoto, Teppei; Miura, Yuuki; Iida, Keiichiro; Uemura, Nozomi; Sugimura, Yoshikuni; Hatakeyama, Shingo; Urushidate, Satoshi; Ohyama, Chikara
Abstract: Aims: To investigate the relationship between urinary urgency (UU) and aponeurotic ptosis (AP) in a health promotion project. Methods: This cross‐sectional study analyzed 658 women in Aomori, Japan. The presence of UU was evaluated using the Overactive Bladder Symptom Score. The distance from the light reflex on the cornea to the upper eyelid (margin reflex distance‐1 [MRD‐1]) was measured. AP was defined as MRD‐1 of less than 2.0 mm. The daily salt intake amount was estimated using the dietary questionnaire. Daily salt intake was defined as excessive if it was 10 g/day or higher. Independent factors of UU and AP were analyzed via multivariable logistic regression model. Results: The number of women with UU and AP was 193 and 65, respectively. Similar background differences were observed in age, cardiovascular disease history, renal function, hypertension, diabetes mellitus, dyslipidemia, and daily salt intake between participants with UU and those with AP. Participants with UU had a higher prevalence of AP (19% vs. 6.2%) than those without. Moreover, more than 50% of the women with AP experienced UU. Multivariable logistic analysis on UU showed that age (≥65 years), diabetes mellitus, daily salt intake (≥10 g/day), and AP (odds ratio, 2.07, p = .014) were independent factors. Multivariable analysis on AP revealed that age (≥65 years), hypertension, daily salt intake (≥10 g/day), and UU were independent factors. Conclusions: AP was an independent indicator of UU, in addition to excessive daily salt intake. Women with AP may tend to intake excessive salt and experience UU.